Patterns of benthic diversity in marine underwater caves of the Marseille Region (France, North-Western Mediterranean Sea) - DERRIEN, MARIE; CHEVALDONNÉ , PIERRE; PÉREZ, THIERRY (Mediterranean Marine Science, 2024)
Underwater caves are remarkable habitats of the Mediterranean Sea. In the present study, we compare the geomorphology of four underwater caves of the Marseille area and the associated sessile assemblages across two contrasted communities (Semi- Dark and Dark-cave communities). Using a non-destructive method of sampling, photoquadrats of the walls of the caves were performed in 2020 to assess the biodiversity and the structure of these communities. In addition, taking advantage of available reference data from 2015, we evaluate the changes in sponge assemblages for the period 2015-2020, focusing on observations of the Semi-Dark cave community. Our results illustrate how the diversity of environmental settings and cave morphologies shape the benthic community composition of the four caves. In all four caves, the Semi-Dark community is the more diverse and harbours the higher number of species when compared to the Dark community. Each cave presents a different species assemblage with in most cases, distinct dominant species which highlight the singularity of each cave. Moreover, our temporal change assessment demonstrates a critical decrease in sponge species richness for all caves, possibly related to the increasing frequency of marine heatwaves that have occurred in the last decade. Although some species (mostly in the Keratosa subclass) seem to be particularly affected, other species such as Chondrosia reniformis appear to have benefitted from the situation. Our findings underline the importance of biodiversity monitoring in a context of a rapidly changing environment, in particular in poorly resilient marine ecosystems such as underwater caves.